2020
DOI: 10.1111/ijlh.13330
|View full text |Cite
|
Sign up to set email alerts
|

The HemoScreen hematology point‐of‐care device is suitable for rapid evaluation of acute leukemia patients

Abstract: Background Hematological patients, receiving intensive chemotherapy (predominantly acute leukemia patients), have repeated postchemotherapy periods with severe bone marrow suppression. As a result, these patients require regular monitoring of the complete blood counts (CBC) for optimal patient care. To reduce the strain on the patient, there is a need for a point‐of‐care (POC) hematology device that provides rapid and reliable results both in general and in cytopenic samples and is suitable for outpatient clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[13,14] Other studies showed that, using the CBC profiles to measure a patient's risk of health outcomes may indicate different infections or leukemia. [16] The rates of RBC were normal in all patients with cancer of various types except one breast cancer patient who had a very low rate of RBC, which indicate some vitamin deficiency or anemia. According to prior studies conducted in 2020, patients are rated based on quantitative changes in blood parameters related to the body's response to stress caused by malignant tumors.…”
Section: Discussionmentioning
confidence: 86%
“…[13,14] Other studies showed that, using the CBC profiles to measure a patient's risk of health outcomes may indicate different infections or leukemia. [16] The rates of RBC were normal in all patients with cancer of various types except one breast cancer patient who had a very low rate of RBC, which indicate some vitamin deficiency or anemia. According to prior studies conducted in 2020, patients are rated based on quantitative changes in blood parameters related to the body's response to stress caused by malignant tumors.…”
Section: Discussionmentioning
confidence: 86%
“…With intensive care patients, HemoScreen gave good correlation for platelet, WBC and red blood cell (RBC) concentrations compared to Sysmex XN, although the bias was positive at higher platelet and WBC concentrations [9]. Another study with acute leukemia patients showed similar trend for platelets and WBC with a good correlation for complete blood count (CBC), absolute neutrophil count and hemoglobin compared to Sysmex XN [10]. None of these studies investigated the performance on full WBC differential or the analyzer's ability to detect WBC abnormalities, even though there is technology and built‐in algorithms for this.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce outpatient supportive care visits, home monitoring of laboratory parameters 6 and home transfusions are possible. Logistically these are difficult as they require significant resources including home nursing, early and systematic sample collection and close outpatient monitoring.…”
mentioning
confidence: 99%